2003
DOI: 10.1007/s00429-002-0286-1
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial anatomic asymmetry in situs inversus totalis

Abstract: Situs inversus is a rare condition in which the position of the thoracic and the abdominal viscera are exchanged from the left to the right sides. A possible inversion of normal dominant intracranial anatomy, has however, rarely been discussed. We examine here the gross anatomy of an elderly cadaveric female for a possible "situs inversus" of the intracranial contents. This study has found that many structures commonly dominant on one side in the intracranial compartment were reversed in this specimen. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…The reason for this atypical presentation is not known. Situs inversus has been previously shown to be associated with abnormal neural axis development and this may lead to variant visceral pain perception (6). Our patient also the pain was located in the retrosternal and right anterior chest.…”
Section: Discussionsupporting
confidence: 51%
“…The reason for this atypical presentation is not known. Situs inversus has been previously shown to be associated with abnormal neural axis development and this may lead to variant visceral pain perception (6). Our patient also the pain was located in the retrosternal and right anterior chest.…”
Section: Discussionsupporting
confidence: 51%
“…Further deviations of the developmental process were clearly involved. Recently, Tubbs et al (2003) reported that intracranial anatomic asymmetry in situs inversus totalis, and more researchers have suggested that situs inversus associated with left-right asymmetry, was likely to be due to genetic abnormalities in the left (Fujiwara et al 2002), nodal (Saijoh et al 2003), inv (Mochizuki et al 1998), Pitxz (Piedra et al 1998) and other genes (Yokoyama et al 1993). Further, the mechanism of other abnormalities such as PDPV and PDCBD are expected to be elucidated along with the elucidation of situs inversus at the level of molecular biology.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting issue regarding such individuals is whether they have reversed brain asymmetries, which could provide a clue to elucidate the developmental mechanisms involved in brain asymmetries. Nevertheless, only few studies have focused on brain asymmetries in individuals with SI [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%